2020
DOI: 10.1515/sjpain-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Associations of neck and shoulder pain with objectively measured physical activity and sedentary time among school-aged children

Abstract: ObjectivesThe potential effects of physical activity and sedentary time on children’s increasing neck and shoulder pain are unclear. The aim of this cross-sectional study was to evaluate the associations between objectively measured physical activity or sedentary time and neck and shoulder pain in children.MethodsChildren (n=905; 10–15 years old) filled in an electronic questionnaire during school hours on the frequency of their neck and shoulder pain. Daytime moderate to vigorous physical activity and sedenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This study is among the first to investigate the prospective associations of the incidence of NSP with accelerometer-measured MVPA and ST in school-aged children. Although the previous cross-sectional studies might lead one to expect that PA would associate with NSP incidence in children 8,9,28 , no such association was found. In support, two previous accelerometer-based studies, differed in some respects from ours, also found no association between PA and the incidence or prevalence of NSP.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This study is among the first to investigate the prospective associations of the incidence of NSP with accelerometer-measured MVPA and ST in school-aged children. Although the previous cross-sectional studies might lead one to expect that PA would associate with NSP incidence in children 8,9,28 , no such association was found. In support, two previous accelerometer-based studies, differed in some respects from ours, also found no association between PA and the incidence or prevalence of NSP.…”
Section: Discussionmentioning
confidence: 75%
“…As a part of a research related to the national "Finnish Schools on the Move" program 9,[19][20][21][22] , 1710 school-aged children in grades 4-7 across Finland were invited to participate in the study. Of these children, 970 participated (mean 12.5 years ± 1.3 years; 52.5% girls) and 684 (75.6%) provided information on all the study variables at baseline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with PIMD have numerous reasons to experience discomfort and pain, and in our study adaptive sports seemed to be able to provide relief and improved comfort (reflecting the physical component of wellbeing) for a majority of children. Sedentary behaviour and low participation in physical activity were reported as risk factors for chronic pain, especially musculoskeletal pain, in typically developing children and adolescents [ 26 , 27 , 28 ], highlighting the value of moderate-to-vigorous physical activity in preventing these symptoms. Beyond their sedentary behaviour, certain children with PIMD present high degrees of physical disuse, which is strongly associated with acute and chronic pain via mechanical hyperalgesia, with peripheral and central sensitization [ 29 ].…”
Section: Discussionmentioning
confidence: 99%